ANALISIS KANDUNGAN LOGAM BERAT TIMBAL (Pb) PADA IKAN PELAGIS KECIL YANG DIDARATKAN DI PPS BELAWAN KECAMATAN MEDAN BELAWAN SUMATERA UTARA - Novita Sari Siboro; Hasan Sitorus; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
The development of the technology has driven the growth of industry, on the one side can increase economic growth, but on the other side can lead to destruction of the environment especially marine organisme that fish due to the negative impact of the waste it generates. The objective of the the research are to analize the heavy metal concentration of Pb in sea water and small pelagic fishes (Decapterus sp, Rastrelliger sp and Sardinella fimbriata) landed at PPS Belawan and analysis the correlation of heavy metal Pb in sea water and body of fishes. The research was conducted at Medan Belawan Subdistrict, North Sumatera Province. Analysis of heavy metal Pb content in sea water and body of fishes was carriedout at the Medan Research and Industry Standarization Laboratory. Result showed that the range concentration of Pb in sea water was 0.17 ppm to 0.20 ppm, while in body of fish of Decapterus sp was 0.50 ppm to 1.18 ppm, Rastrelliger sp was 0.24 ppmto 0.97 ppm and Sardinella fimbriata was 0.23 ppm to 0.50 ppm. Compared to Regulation of National Standarization on 2004 the concentration of heavy metal Pb in body fishes had exceeded the level standard of 0.2 ppm. Based on the regresion analysis the correlation (r) of heavy metal contentration in sea water was very strong to heavy metal concentration in body fishes with value 0.73.Keywords : Plumbum, Sea Water, Small Pelagic Fish, Belawan